# How do I evaluate \lim_{z \to 1}(1-z)\tan \frac{\pi z}{2} I tried

How do I evaluate $$\displaystyle\lim_{{{z}\to{1}}}{\left({1}-{z}\right)}{\tan{{\frac{{\pi{z}}}{{{2}}}}}}$$
I tried using the identity, $$\displaystyle{\tan{{\frac{{{x}}}{{{2}}}}}}={\frac{{{1}-{\cos{{x}}}}}{{{\sin{{x}}}}}}$$ to simplify this to:
$$\displaystyle\lim_{{{z}\to{1}}}{\left({1}-{z}\right)}{\frac{{{\sin{\pi}}{z}}}{{{1}+{\cos{\pi}}{z}}}}$$

• Questions are typically answered in as fast as 30 minutes

### Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it

psor32
Note that
$$\displaystyle{\tan{{\left({\frac{{\pi{z}}}{{{2}}}}\right)}}}={\tan{{\left({\frac{{\pi{\left({z}-{1}\right)}}}{{{2}}}}+{\frac{{\pi}}{{{2}}}}\right)}}}$$
$$\displaystyle=-{\cot{{\left({\frac{{\pi}}{{{2}}}}{\left({z}-{1}\right)}\right)}}}$$
and that therefore
$$\displaystyle\lim_{{{z}\to{1}}}{\left({1}-{z}\right)}{\tan{{\left({\frac{{\pi{z}}}{{{2}}}}\right)}}}=\lim_{{{z}\to{1}}}{\left({\frac{{{z}-{1}}}{{{\sin{{\left({\frac{{\pi}}{{{2}}}}{\left({z}-{1}\right)}\right)}}}}}}\times{\cos{{\left({\frac{{\pi}}{{{2}}}}{\left({z}-{1}\right)}\right)}}}\right)}$$
$$\displaystyle={\frac{{\lim_{{{z}\to{1}}}{\cos{{\left({\frac{{\pi}}{{{2}}}}{\left({z}-{1}\right)}\right)}}}}}{{\lim_{{{z}\to{1}}}{\frac{{{\sin{{\left({\frac{{\pi}}{{{2}}}}{\left({z}-{1}\right)}\right)}}}}}{{{z}-{1}}}}}}}$$ (since both limits exist)
$$\displaystyle={\frac{{{\cos{{0}}}}}{{{\frac{{\pi}}{{{2}}}}{\cos{{0}}}}}}$$
$$\displaystyle={\frac{{{2}}}{{\pi}}}$$
###### Not exactly what you’re looking for?
maul124uk
Let $$\displaystyle{t}\:={\frac{{\pi}}{{{2}}}}{\left({1}-{z}\right)}$$
$$\displaystyle\lim_{{{z}\to{1}}}{\left({1}-{z}\right)}{\tan{{\frac{{\pi{z}}}{{{2}}}}}}=$$
$$\displaystyle={\frac{{{2}}}{{\pi}}}\lim_{{{t}\to{0}}}{t}{\cot{{t}}}=$$
$$\displaystyle={\frac{{{2}}}{{\pi}}}\lim_{{{t}\to{0}}}{\frac{{{t}}}{{{\sin{{t}}}}}}\cdot\lim_{{{t}\to{0}}}{\cos{{t}}}$$
Vasquez

$$\lim_{z \to 1} \frac{\cos(\frac{\pi z}{2})}{1-z}=-\lim_{z \to 1} \frac{\cos(\frac{\pi z}{2})-\cos(\frac{\pi}{2})}{z-1}=-\cos(\frac{\pi x}{2})' \Bigg|_{x=1}=\frac{\pi}{2}\sin (\frac{\pi}{2})=\frac{\pi}{2}$$
and
$$\lim_{z \to 1} \sin \frac{\pi z}{2}=1$$
Combining the above two
$$\lim_{z \to 1}(1-z)\tan(\frac{\pi z}{2})=\lim_{z \to 1} \frac{1-z}{\cos(\frac{\pi z}{2})} \cdot \lim_{z \to 1} \sin(\frac{\pi z}{2})=\frac{2}{\pi} \cdot 1$$